Production of Plant-Derived Oleuropein Aglycone by a Combined Membrane Process and Evaluation of Its Breast Anticancer Properties - Mazzei, Rosalinda; Piacentini, Emma; Nardi, Monica; Poerio, Teresa; Bazzarelli, Fabio; Procopio, Antonio; Di Gioia, Maria Luisa; Rizza, Pietro; Ceraldi, Rosangela; Morelli, Catia; Giorno, Lidietta; Pellegrino, Michele (Frontiers in Bioengineering and Biotechnology, 2020)
Natural product research and herbal therapies have become thriving fields of research. The production of plant-derived compounds with attractive biological activity by synthetic methods is highly required. The conventional commercial production, by chemical synthesis or solvent extraction, is still not economical and sustainable, mainly because it involves many steps, uses toxic solvents, and usually ends up with a low yield of the target product that is often mixed with various structurally similar byproducts. For this reason, alternative, sustainable, greener and highly efficient processes are required. Membrane processes are worldwide recognized as green technologies since promote process integration, materials diversity, energy saving, waste minimization, efficient separation processes etc. The present article attempts to describe the production, characterization, and utilization of bioactive compounds derived from renewable waste material (olive leaves) as drug candidates in breast cancer treatment. In particular, an integrated membrane process (composed by a membrane bioreactor (MBR) and a membrane emulsification (ME) system) has been developed for the production of a purified non-commercially available phytotherapic: the oleuropein aglycone (OLA). The method permits to achieve a 93% of conversion of the substrate (oleuropein) and to extract the compound of interest with 90% of efficiency in sustainable conditions. The bioderived compound showed antiproliferative and pro-apoptotic activities against breast cancer cells in vitro, suggesting it as a potential agent for breast cancer treatment, also in the occurrence of resistance to hormonal therapies.